The knowledge management strategies used as a tool within and through strategic consulting firms to increase the organisational performance - Mohamed Mahmoud, Fatimetou Zahra; Mohamed Mahmoud, Ahmed; Ibrahim, Jamaludin (IJSRP.ORG, 2015)
As a matter of fact, the rising awareness in organisations to not focus only in the physical assets in the organisation but also in other paramount assets such as knowledge was the launching point for organisations to go to the implementation of knowledge management and creating knowledge management strategies codified or personalized in order to overcome issues and plan for its future sustainability and development. Actually, the implementation of knowledge management strategy is the strategic consulting company internal asset and external mean to get value. Although, after the implementation of knowledge management strategy in some companies they face the problem of the low revenue and efficiency of the strategy implemented. That’s why the combination of the codification and personalization make the organisation able to create, share, save and re-use knowledge and exchange it in the organisation using technology or informal communication networks in order to raise the innovation in the work environment and the creation of new ideas and services. Also, this knowledge stored and codified especially about the organization customers can be considered as the basic knowledge to take the strategic decisions and by KM the organisation will be able to extract, understand and well use this knowledge in order to strengthen the relation with its customers and allow them to become the organisation’s partners and advisors. Indeed, that’s mean that the organisation strategy must be renewable and in corporation with the overall business model and focus on the core competence in the organisation and the management of the customer knowledge and interactions, this will influence positively and upgrade the organisational performance in any organisation.